Criação de linha de produtos químicos para tratamento de águas de piscina - Rosa, Tássia Warken da (Universidade do Vale do Rio dos Sinos, 2015)
This course conclusion paper adresses the topic of developing a complete product line for residential pool water treatment and the development of the respective brand, in a company that already works with water treatment chemicals for industrial Waters for over 20 years. The project is justified as a strategy to diversify the company’s portfólio, once it already has an advanced structure able to support the development of such products, in a market that allows high margins. As a general objetive, this study intends to elaborate the Project Plan in order to convince the company’s shareholders to sponsor its execution. The plan was based on Project Management good practices appointed in PMBOK 5th edition, aiming at meeting expectations regarding quality, time and budget and allow project controlling during its execution
Keywords: Gestão de projetos; Plano de projeto; Desenvolvimento de produtos; Diversificação de portfólio; Project management; Project plan; Product development; Portfolio diversification